Beyond the Surface: Exploring the Next Level of Terrorism on the Dark Web - Mappaselleng, Nur Fadhilah; Kadir, Nadiah Khaeriah; Ahmad, Abd. Kadir; Kadir, Zul Khaidir; Normiati, Normiati (Universitas Negeri Gorontalo, 2025)
The lack of effective security mechanisms on the Surface Web facilitates the occurrence of cybercrime. The high accessibility of the Surface Web also allows law enforcement agencies to more easily track and identify perpetrators. However, this motivates criminals to migrate to the Dark Web, the deepest layer of the internet that offers a higher level of security. This research aims to analyze the communication patterns utilized by terrorists on the dark web, propaganda, recruitment, and the use of cryptocurrency in transactions and fundraising by terrorists. The research method used is normative legal research with a conceptual and case approaches and qualitative analysis. This research analyses that terrorists have transitioned to using the Dark Net in a similar manner to how they have utilized the Surface Web over the past several decades, but there are now additional opportunities for tech-savvy operatives. Three main features, anonymity, encrypted messaging, and the use of cryptocurrency, work together to provide an environment that is almost perfect for terrorists on the Dark Web. This combination allows terrorists to conduct their operations more effectively and covertly, making the Dark Web a highly valuable tool for achieving their goals without significant risk of exposure and disruption by security authorities.